Reading the prophets as Christian scripture : a literary, canonical, and theological introduction - Tully, Eric J. (Grand Rapids, MI : : Baker Academic, a division of Baker Publishing Group, 2022)
"This book offers an accessible introduction to the prophetic books of the Old Testament, grounded in the view that these books should be read as Christian Scripture"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. Prophets -- Criticism, interpretation, etc